Firms in open source software development : Managing innovation beyond firm boundaries - Schaarschmidt, Mario (Gabler Verlag, 2012)
In open innovation scenarios, firms are able to profit from technological developments that take place beyond their legal boundaries. However, in the absence of contract-based vertical command chains, such as in the case of open source software (OSS), it is difficult for firms to obtain control over the innovation project's trajectory. In this book, the author suggests that firms have basically two options to control project work beyond their boundaries and beyond their vertical command chains. The assumption is discussed against various theories of the firm as well as control theory and empirically tested by analyzing firm engagement in Eclipse open source projects as well as communication work in the Linux kernel project.